Engineering in clothing design: method of teaching - Atrakhovich, Elena I. (Human in the Socio-Cultural Dimension, 2020)
In the article the basic trends of development of the Belarusian school of costume design up-to-date are disclosed. The basic approaches to costume project-making reflected in the creative works of designers are systemized. The article analyzes modern methods of design engineering and their relationship with the development of educational methods in the field of design training. In addition, the author considers the issues of teaching methods of special disciplines in the field of design, as well as the problems of forming a unified approach to the model of a specialist in the field of national design education.